Advances in enhancing the light extraction efficiency of AlGaN-based deep ultraviolet light-emitting diodes via optical polarization - Zhu, Dong-Xu; Wang, Gong; Li, Yun-Fei (Frontiers in Physics, 2025)
AlGaN-based deep ultraviolet light-emitting diodes (DUV-LEDs), as a novel solid-state ultraviolet light source, compared with the traditional ones, have competitive advantages over traditional UV sources such as mercury (Hg) pollution free, low energy consumption, small size, and tunable wavelengths. They hold broad prospects for development in critical fields including air purification, water disinfection, biosensing, and communications. Enhancing the electro-optical conversion efficiency of DUV-LEDs is essential for achieving large-scale commercial applications in disinfection and sterilization. Improving the device’s relatively low light extraction efficiency (LEE) has proven to be an effective strategy for boosting electro-optical efficiency and overcoming technical barriers. In this review, the fundamental configurations of the AlGaN DUV-LEDs and the regulatory logic of optical polarization characteristics on LEE are summarized. The detailed discussions include the recent research advances in improving the LEE of the DUV-LEDs via optical polarization—specifically by adjusting quantum well structures, optimizing polarization-dependent light propagation paths, and incorporating additional reflection/diffraction structures. Furthermore, it outlines the challenges and development prospects for improving LEE at the optical polarization level.